Cloud chamber experiments on the origin of ice crystal complexity in cirrus clouds - Schnaiter, Martin; Järvinen, Emma; Vochezer, Paul; Abdelmonem, Ahmed; Wagner, Robert; Jourdan, Olivier; Mioche, Guillaume; Shcherbakov, Valery N.; Schmitt, Carl G.; Tricoli, Ugo; Ulanowski, Zbigniew; Heymsfield, Andrew J. (Atmospheric chemistry and physics, 2016)
This study reports on the origin of small-scale ice crystal complexity and its influence on the angular light scattering properties of cirrus clouds. Cloud simulation experiments were conducted at the AIDA (Aerosol Interactions and Dynamics in the Atmosphere) cloud chamber of the Karlsruhe Institute of Technology (KIT). A new experimental procedure was applied to grow and sublimate ice particles at defined super- and subsaturated ice conditions and for temperatures in the −40 to −60 °C range.
Gesehen am 19.05.2020